2023
DOI: 10.3390/f14050942
|View full text |Cite
|
Sign up to set email alerts
|

Species Composition and Seasonal Abundance of Predatory Mites (Acari: Phytoseiidae) Inhabiting Aesculus hippocastanum (Sapindaceae)

Abstract: Species of the family Phytoseiidae (Acari: Mesostigmata) inhabit a wide range of herbs, shrubs, and trees. Horse chestnut, Aesculus hippocastanum, is an important ornamental tree in Europe and, in addition to its importance for pollinators, it can serve as a host plant of these predatory mites. Little is, however, known about the factors affecting spatiotemporal variability in the density of phytoseiids on A. hippocastanum in an urban environment. We therefore assessed the species composition and the spatial a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Trichomes aid in retaining moisture and high levels of humidity within domatia, thus creating favourable conditions for mites and their eggs [8,19]. Additionally, Kopačka [10] found that leaf age and percentage greenness affected seasonal mite abundance. Other factors, such as the density of mite prey and the availability of alternative food sources, may also influence mite diversity and abundance, and studies have found that seasonal fluctuations in abundance are related to the availability of pollen and fungi [19,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trichomes aid in retaining moisture and high levels of humidity within domatia, thus creating favourable conditions for mites and their eggs [8,19]. Additionally, Kopačka [10] found that leaf age and percentage greenness affected seasonal mite abundance. Other factors, such as the density of mite prey and the availability of alternative food sources, may also influence mite diversity and abundance, and studies have found that seasonal fluctuations in abundance are related to the availability of pollen and fungi [19,22].…”
Section: Discussionmentioning
confidence: 99%
“…In temperate zones, mites appear on deciduous trees annually in spring, and the diversity of these communities changes every season. Seasonal changes are sometimes driven by vegetation, the overall greenness of the plant [5,10], the availability of food and fungal flora, and leaf architecture [7]. A study on four varieties of grapes with different leaf architecture documented high densities of phytoseiid mites from late April to late June during spring and low densities in September and October in the autumn months in vineyards [11,12].…”
Section: Introductionmentioning
confidence: 99%